Zeolite and bentonite as caesium binders in reindeer feed - Åhman, Birgitta; Forberg, Sevald; Åhman, Gustaf (Rangifer, 1990)
The effects of zeolite and bentonite on the accumulation and excretion of radiocaesium (Cs-137) in reindeer were studied in two feeding experiments. Six animals in each experiment were given lichens contaminated with radiocaesium from fallout after the Chernobyl nuclear power plant accident. In addition, they were fed pellets containing bentonite (Experiment I) or zeolite (Experiment II). Two animals, controls, in each experiment received no caesium-binder. The activity concentration of radiocaesium in blood was used to evalute the radiocaesium level in the body. Faeces and urine were collected to measue the excration of radiocaesium. The animals in Experiment I were depleted of radiocaesium before the start of the experiment. After three weeks, with an intake of 17 - 18 kBq Cs-137/day, the controls had reached activity concentrations of radiocaesium in blood corresponding to 4 - 4.5 kBq Cs-137/kg in muscle. Reindeer fed 23 or 46 g of bentonite per day stabilized at values below 0.8 kfiq/kg in muscle. In Experiment II, the reindeer started with radiocaesium activity concentrations in blood corresponding to 2 - 4.5 kBq Cs-137/kg in muscle. After four weeks of feeding, with an intake at about 8.5 kBq Cs-137/day, controls had increased their radiocaesium values by an average of 40%. Reindeer receiving 25 or 50 g zeolite per day decreased with 18 and 45%, respectively. Net absorption of radiocaesium from the gastro-intestinal tract was calculated at 50 -70% in animals receiving no caesium-binder. Reindeer fed bentonite had an absorption below 10% while those fed zeolite absorbed around 35%.